Output feedback L1 finite-time control of switched positive delayed systems with MDADT. (February 2015) - Liu, Jiao; Lian, Jie; Zhuang, Yan
Abstract: In this paper, the problem of static output-feedback L 1 finite-time control for switched positive systems with time-varying delay is investigated. Mode-dependent average dwell time (MDADT) approach, which permits each subsystem to have its own average dwell time, is adopted in this paper to reduce the conservativeness of the average dwell time method. By constructing multiple linear copositive Lyapunov functions (MLCLFs), static output-feedback controllers are designed and a sufficient condition is derived to ensure that the closed-loop system is positive and L 1 finite-time bounded. Finally, a simulation example is given to illustrate the effectiveness and potential of the proposed method.